Early platelet recovery following cardiac surgery with cardiopulmonary bypass. (16th November 2016) - Van Poucke, Sven; Stevens, Kris; Wetzels, Rick; Kicken, Cécile; Verhezen, Paul; Theunissen, Maurice; Kuiper, Gerhardus; van Oerle, Rene; Henskens, Yvonne; Lancé, Marcus
Abstract: Coronary artery bypass grafting (CABG) with cardiopulmonary bypass (CPB) is frequently associated with low platelet count (PC) and disturbed platelet function (PF). While PC is easy to measure, PF is more difficult to assess. Moreover, the time-related platelet dysfunction and recovery after CPB is not fully elucidated. Platelet dysfunction could lead to bleeding but also to coronary graft failure. Laboratory tests could provide more insights into PF after CABG. The aim of the current study was to investigate the time-related PF induced by CPB. Blood samples of 20 patients with a preoperative PC of more than 250 × 10 9 /L were collected before incision, after weaning from CPB, and 24 h postoperative. Platelet contribution to coagulation was quantified by PLTEM (calculated by means of EXTEM and FIBTEM results). PF was assessed by multiple electrode impedance aggregometry (MEIA) in whole blood and by light transmission aggregometry (LTA) in platelet-rich plasma after stimulation with arachidonic acid (AA), adenosine diphosphate, collagen, and thrombin-receptor-activating peptide. LTA and MEIA analysis demonstrated significant platelet dysfunction after CPB, with partial recovery within 24 h after surgery. AA-induced platelet aggregation increased to higher levels within 24 h after surgery compared to baseline values as measured by LTA. PLTEM maximum clot firmness remained unchanged throughout the study. Correlation analyses revealed that MEIA and rotational thromboelastometry (ROTEM), but not LTA, were dependent on PC and hematocrit. No correlations were found between LTA, MEIA, ROTEM, PC, and clinical outcome parameters. Our results demonstrate a reversible platelet dysfunction recovering within 24 h after CPB. Interestingly, AA-induced platelet aggregation increases to higher levels during the first 24 h postoperatively, which might be important for early initiation of antiplatelet therapy after CABG. MEIA as POC test is able to detect platelet dysfunction during cardiac surgery with a PC of ≥150 × 10 9 /L.